External impacts on SiC nanostructures in pure and lightly doped silicon carbide crystals - Vlaskina, S.I.; Mishinova, G.N.; Vlaskin, V.I.; Rodionov, V.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Influence of plastic deformation and high-temperature annealing (T = 2100 °C, t = 1 h) on SiC crystals with grown polytypic junctions demonstrating SF and DL spectra have been presented. SF-i and DL-i type luminescence are inherent to SiC crystals with distortions of the structure related with availability of packing defects that lead to onedimensional disordering (along the c-axis). They are a most expressed in doped crystals with original growth defects. DL luminescence appears in pure crystals at plastic deformation and in doped crystals at a hydrostatic pressure. It enhances at the high temperature annealing, too.